2015
DOI: 10.1186/1477-7819-13-1
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis of nasopharyngeal carcinoma to parotid lymph nodes: a retrospective study

Abstract: BackgroundMalignant parotid tumors are rare metastases originating from nasopharyngeal carcinoma (NPC). This study aimed to investigate the clinicopathological features and outcome of patients with metastasis of NPC to parotid lymph nodes after surgical therapy.MethodsWe enrolled 14 NPC patients who had metastatic disease to parotid lymph nodes after IMRT. They received surgical treatment by total parotidectomy with neck dissection, superficial parotidectomy with neck dissection, partial parotidectomy with nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 13 publications
4
64
0
Order By: Relevance
“…Metastatic disease to the parotid lymph nodes typically originate from head and neck lesions, with numerous large case series clearly establishing the clinical outcomes from cutaneous (SCC and melanoma) and mucosal (oropharyngeal) primary sites 12 13. Although there are no reported cases arising from the nasal septum, there are several documented incidents of nasopharyngeal SCC metastasising to the parotid gland 14–17. Despite there being no general consensus on the definitive management of these lesions, they all share a similar initial surgical intervention to our case including parotidectomy with or without neck dissection.…”
Section: Discussionsupporting
confidence: 54%
“…Metastatic disease to the parotid lymph nodes typically originate from head and neck lesions, with numerous large case series clearly establishing the clinical outcomes from cutaneous (SCC and melanoma) and mucosal (oropharyngeal) primary sites 12 13. Although there are no reported cases arising from the nasal septum, there are several documented incidents of nasopharyngeal SCC metastasising to the parotid gland 14–17. Despite there being no general consensus on the definitive management of these lesions, they all share a similar initial surgical intervention to our case including parotidectomy with or without neck dissection.…”
Section: Discussionsupporting
confidence: 54%
“…Down-regulating the nuclear β-catenin reduces the interaction of β-catenin and TCF/LEF, thereby suppressing the Wnt signaling pathway24. Herein, we also showed that the suppression of the nuclear translocation of β-catenin resulted in the down-regulated expression of cyclin D1 and c-myc, which were downstream oncogenes of the Wnt/β-catenin signaling pathway2526. Cyclin D1 participates in the phase transitions of the cell cycle by phosphorylating the retinoblastoma protein.…”
Section: Discussionmentioning
confidence: 69%
“…For example, a direct relation among oxidative stress, DNA damage and elevated frequency of p53 mutation in CRC has been observed 23 . Most extensively studied endogenous DNA damage by ROS is the formation of 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodG) 31 . As the biomarker of oxidative stress, 8-oxodG level is higher in colorectal tumors than in normal mucosa 31 .…”
Section: The Relation Between Oxidative Stress and Crcmentioning
confidence: 99%
“…Most extensively studied endogenous DNA damage by ROS is the formation of 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodG) 31 . As the biomarker of oxidative stress, 8-oxodG level is higher in colorectal tumors than in normal mucosa 31 . Moreover, increased 8-oxodG is also found in leukocytes and urine of CRC patients 32 .…”
Section: The Relation Between Oxidative Stress and Crcmentioning
confidence: 99%